Ferroptosis, pathogenesis and therapy in AS co-depression disease - Zhao, Yulong; Ren, Peng; Luo, Qiang; Li, Xue; Cheng, Xinyi; Wen, Youliang; Wu, Xiaoyun; Zhou, Junjie (Frontiers in Pharmacology, 2025)
Atherosclerosis (AS)-related cardiovascular disease and depression are often comorbid, with patients with cardiovascular disease facing an increased risk of depression, which worsens AS. Both diseases are characterized by oxidative stress and lipid metabolism disorders. Ferroptosis, a form of cell death characterized by iron overload and harmful lipid peroxide accumulation, is found in various diseases, including AS and depression. Consistent with the iron deposition and lipid peroxidation (LPO) that characterize the ferroptosis mechanism, disturbances in iron and lipid metabolism are also crucial pathogenic mechanisms in AS and depression. The comorbid mechanisms are complex, posing challenges for clinical treatment. Chinese herbs hold significant potential owing to their multi-target pharmacological effects. Therefore, this review aims to investigate iron overload, LPO, and ferroptosis across various cell types, the shared pathogenesis of AS and depression with ferroptosis, and research on Chinese herbal medicine targeting ferroptosis in the treatment of anti-AS co-depression. This provides a comprehensive understanding of AS co-depression disease from the perspective of ferroptosis.